Potential efficacy of dopamine loaded‐PVP/PAA nanogel in experimental models of Parkinsonism: Possible disease modifying activity. Issue 5 (22nd August 2014) - Rashed, Engy R.; Abd El‐Rehim, Hassan A.; El‐Ghazaly, Mona A.
Abstract: This study aimed to investigate the ability of dopamine (DA)‐loaded polyvinylpyrrolidone‐poly(acrylic acid) (PVP/PAAc) nanogel [synthesized by gamma (γ) radiation‐induced template polymerization] [Nano‐DA] to deliver DA across the blood brain barrier, and to evaluate the efficacy and safety of the acute and subchronic administration of Nano‐DA in modulating motor activity and/or the biochemical changes in rat brain; induced by different models of Parkinsonism. In this respect, (PVP/PAAc) nanogel was synthesized by gamma radiation‐induced polymerization of acrylic acid (AAc) in an aqueous solution of PVP as a template polymer, and then, it was used as a nano‐drug carrier for DA. The PVP/PAAc and (PVP/PAAc loaded‐DA nanogel particles were characterized by dynamic light scattering, infrared spectroscopy, and field emission‐scanning electron microscopy. The loaded gel was administered in different doses and dosing regimens to Parkinsonian rats, and the catalepsy score and striatal DA levels were assessed. Then, the potential disease‐modifying activity of this form of DA was investigated, through the assessment of the improvement in mitochondrial function, following the subchronic administration of Nano‐DA to Parkinsonian rats. Significant disease‐modifying effects were observed upon the administration of Nano‐DA; in addition to normalization in their motor activity. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1713–1720, 2015.